Klepon Si Centing: Training of breastfeeding counsellor cadres to prevent stunting in Cimahi City - Erni Hernawati; Dini Nurdiani; Dionisia Cornelia Rahandity; Eka Febriyanti Hartini; Elis Hijriah Handayani; Fuji Ratna Sari Priatna; Idah Handayani; Irrena Apriliani; Leni Maelani; Marlina; Rizqa Anna Umilla; Siti Masriyah; Suminar; Yuan Prihatin Ningrum (LPPM Politeknik Sandi Karsa, 2025)
Stunting is a chronic nutritional problem that is still a public health challenge in Indonesia, including in Cimahi City, which has a stunting prevalence of 9.4%. One of the efforts to prevent stunting is increasing exclusive breastfeeding coverage, which is still below the national target. This community service activity aims to increase the capacity of health cadres in breastfeeding counselling knowledge and skills through intensive community-based training. The program will be carried out in March 2025 in RW 06 Melong Village, the working area of the Central Melong Health Centre, Cimahi City, with eight cadre participants. Evaluation was carried out through pre-test and post-test using a questionnaire consisting of 20 questions that had been tested for validity and reliability, as well as participatory observation of changes in attitudes and skills of cadres. The results showed an increase in the average knowledge score of 33.1 points with a significant paired t-test result (p = 0.001). Qualitatively, participants showed increased self-confidence, skills in practising lactation techniques and oxytocin massage, and initiatives to form breastfeeding support groups to sustain education. This program contributes to cadre empowerment and is a potential strategy to support the acceleration of stunting reduction at the community level